1998
DOI: 10.4067/s0717-71781998002600009
|View full text |Cite
|
Sign up to set email alerts
|

Validación de la hipótesis de mortalidad por inanición en larvas de Engraulis ringens Jenyns, 1842 (Pisces: Engraulidae), utilizando el criterio histológico en un área de surgencia costera en el norte de Chile

Abstract: RESUMEN. Se analiza la hipótesis de inanición como causa de la mortalidad natural en larvas de Engraulis ringens (anchoveta), en la época de otoño (abril) de 1989, en un área de surgencia costera del norte de Chile (20º30'S-21º45'S). La condición nutricional de las larvas se determinó por criterios histológicos, examinando los tejidos del hígado, páncreas, intestino medio, musculatura, notocorda y cartílago. Se estudio un total de 6.226 larvas. La principal distribución espacial se presentó de 1 a 10 mn de la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…However, differences in otolith growth patterns between autumn-winter and spring-summer cohorts are not so marked, which is indicative of favourable conditions for early growth for these species all year round. Indeed, some studies on the feeding of larval fish have demonstrated that although larval food abundance may vary among seasons and localities along the HCS in Chile, starvation due to limited food availability alone does not seem to be such a common feature in this species, even in seasons of lower production (autumn and winter; Pizarro et al 1998;Thiel et al 2007). Moreover, for E. ringens in northern Chile, a low incidence of starvation was reported during autumn (Pizarro et al 1998).…”
Section: Fast Growth Before Recruitmentmentioning
confidence: 99%
“…However, differences in otolith growth patterns between autumn-winter and spring-summer cohorts are not so marked, which is indicative of favourable conditions for early growth for these species all year round. Indeed, some studies on the feeding of larval fish have demonstrated that although larval food abundance may vary among seasons and localities along the HCS in Chile, starvation due to limited food availability alone does not seem to be such a common feature in this species, even in seasons of lower production (autumn and winter; Pizarro et al 1998;Thiel et al 2007). Moreover, for E. ringens in northern Chile, a low incidence of starvation was reported during autumn (Pizarro et al 1998).…”
Section: Fast Growth Before Recruitmentmentioning
confidence: 99%
“…Despite the high environmental heterogeneity linked to the upwelling circulation within Mejillones Bay, the distribution patterns of the coastal pelagic fish larvae in northern Chile usually show a direct relationship with high chlorophyll concentrations, since it shows high concentration (5 mg m ) from coast to 20 km offshore (Yuras et al, 2005), in the same areas where spawning of clupeiform fishes occur (Morales et al, 1996). This spatial pattern may explain the reduced starvation mortality estimated for anchovy larvae detected by Pizarro et al (1998).…”
Section: Discussionmentioning
confidence: 93%
“…Off northern Chilean coast presence of dense abundances of phyto-and zooplankton near surface and nearshore during the spawning period (austral winter) could facilitate a successful larval feeding (Escribano, 1998;Escribano & Hidalgo, 2000;Herrera & Escribano, 2006). However, the cross-shelf currents derived from the upwelling process may cause significant offshore transport of fish eggs and larvae as well as mortality due starvation in fish larvae advected to oceanic waters (Pizarro et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Long term tissues (muscle, notochord, cartilage, and nervous system) only showed histological changes under extreme starvation suffered from starved treatment larvae and only few studies have analyzed their response to starvation (O'Connell, 1976;Uriarte & Balbontín, 1987;Pizarro et al, 1998;Catalán & Olivar, 2002;Catalán, 2003). On the other hand, short term tissues (gut, liver, and pancreas) have been widely used and probed to be more sensitive to starvation than long term tissues (Sieg, 1998;Chen et al, 2007;Diaz et al, 2011).…”
Section: Discussionmentioning
confidence: 99%